The high prevalence of the I27 mutant HBcAg18-27 epitope in Chinese HBV-infected patients and its cross-reactivity with the V27 prototype epitope - Liu, Heng-Gui (Clinical immunology (Orlando, Fla.), 2007)
HBcAg18-27 (FLPSDFFPSV, V27 epitope) is a dominant HLA-A2-restricted epitope in hepatitis B virus (HBV)-infected patients. So far, the occurrence of the epitope has not been assessed in China, where the prevalence of chronic HBV infection is high. In this report, we sequenced the HBV core gene in 105 Chinese patients with chronic HBV infection. Approximately 93.3% (98/105) of the core genes that were sequenced contained mutations with amino acid substitution at position 27 of the core protein: a mutation from a valine to an isoleucine (V27I). The mutant peptide (FLPSDFFPSI, I27) was found to bind to the HLA-A2 molecule with high affinity and elicit specific cytotoxic T lymphocyte (CTL) responses in acutely infected hepatitis B patients. In CTL assays using I27-specific pentamer staining, the V27 epitope showed a cross-reactive T cell response specific for the I27 epitope, but not vice versa. These findings provide important insights for the design of HBcAg18-27-based vaccines in the future